The impact of access to sanitary toilets on rural adult residents' health: Evidence from the China family panel survey - Chen, Baoqi; Jin, Fulei; Zhu, Yaxin (Frontiers in Public Health, 2022)
Toilet sanitation is related to public health and environmental protection. In the context of toilet revolution in rural China, this study used ordered probit regression analysis to evaluate the impact of access to sanitary toilets on rural residents’ health. Based on the data from the China Family Panel Study (CFPS) in 2014, we found that access to sanitary toilets in rural households significantly improved residents’ health, which was proved robust by a series of checks. Mechanism analysis showed that preventing faeces from contaminating water sources was the important mechanism for using sanitary toilets to improve health. In addition, we found that the impact of access to sanitary toilets was more pronounced among female, middle-aged, and low-income people. These findings show that toilet revolution has important significance for residents’ health and protection of water sources. Consequently, to improve public health, it is imperative for the governments in developing countries to invest in sanitary toilets.